O muzykoterapii kreatywnej dziecka w wieku przedszkolnym = Issues on creative music therapy for children of preschool age - Szymajda, Agnieszka (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The paper presents possibilities of using creative music therapy in work with children of preschool age. It discusses the main assumptions of the Nordoff- Robbins concept in the context of the needs of a small child. The concept presented in this study is a broad, holistic approach to the subject and is the result of research based on experimental and qualitative case studies. In this perspective, creative music therapy enters "new areas", which haven`t before been intended for it.
Keywords: muzykoterapia kreatywna; wychowanie przedszkolne; pedagogika włączająca; creative music therapy; pre-primary education; inclusive pedagogy